ESG and Financial Performance: A Comparative Study of Listed and Non-Listed Mining Companies in the SRI-KEHATI Index - Emilda, Emilda; Nurkholis, Kgs. M.; Lestari, Amelia (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to analyze the relationship between Environmental, Social, and Governance (ESG) scores and Return on Assets (ROA) in mining sector companies listed and not listed in the SRI-KEHATI index. The background of this research is based on the importance of implementing sustainability principles in company operations and how these principles affect financial performance. This study uses a quantitative approach with descriptive analysis methods and two statistical tests, namely the Independent Sample t-test for the risk variable and the coefficient of variation, and the Mann-Whitney U Test for the return variable. Data was obtained from the company's annual report for the 2019-2023 period. The results showed that companies incorporated in the SRI-KEHATI index have higher ESG scores than companies that are not incorporated. However, there is no significant difference in risk and return between the two groups of companies. In addition, there is a positive trend between increasing ESG scores and financial performance (ROA). The implications of these findings suggest that a commitment to sustainability can strengthen reputation and improve the efficiency and long-term financial stability of companies. Keywords: ESG; SRI-KEHATI; financial performance; profitability; mining companies